2018
DOI: 10.1186/s13073-018-0612-8
|View full text |Cite
|
Sign up to set email alerts
|

Mechanisms of PARP inhibitor resistance in cancer and insights into the DNA damage response

Abstract: Editorial summaryInhibitors of poly(ADP-ribose) polymerase (PARPi) have entered the clinic for the treatment of patients with cancers that lack homology-directed DNA repair, but drug resistance remains a clinical hurdle. Recent advances in the identification of PARPi resistance mechanisms have yielded a better understanding of DNA end protection and the relevance of endogenous poly(ADP-ribose) glycohydrolase, highlighting new vulnerabilities.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
73
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 80 publications
(73 citation statements)
references
References 11 publications
0
73
0
Order By: Relevance
“…Loss of 53BP1 function by either mutation or downregulation accelerates the BRCA1-independent endresection and provides PARP inhibitor resistance [111]. It has been demonstrated that the inactivation of downstream factors of 53BP1-mediated repair, typically RIF1 and REV7, also leads to the restoration of DNA end resection, and consequently promotes homology-mediated repair [112]. Loss of the 53BP1-RIF1-REV7 pathway in PARP inhibitorresistant BRCA1-deficient cells results in hypersensitivity to ionizing radiation.…”
Section: Parp Inhibitors Resistancementioning
confidence: 99%
“…Loss of 53BP1 function by either mutation or downregulation accelerates the BRCA1-independent endresection and provides PARP inhibitor resistance [111]. It has been demonstrated that the inactivation of downstream factors of 53BP1-mediated repair, typically RIF1 and REV7, also leads to the restoration of DNA end resection, and consequently promotes homology-mediated repair [112]. Loss of the 53BP1-RIF1-REV7 pathway in PARP inhibitorresistant BRCA1-deficient cells results in hypersensitivity to ionizing radiation.…”
Section: Parp Inhibitors Resistancementioning
confidence: 99%
“…These outcomes reveal additional cGAS functions, which could be used to understand its contribution to diseases related to genome instability 189. In another study, cGAS has recently been shown to associate genomic instability with the innate immune response 190. Lately, it is uncovered in mouse and human models that cGAS hinders HR.…”
Section: The Cgas‐sting Pathway For Tumorigenesis and Immunotherapy Rmentioning
confidence: 98%
“…The ensuing DNA damage incites molecular relocation of cGAS in a manner reliant on importin‐α, and the consequent phosphorylation of cGAS at the site of tyrosine 215 induced by B‐lymphoid tyrosine kinase, which encourages the intracellular cytosolic maintenance of cGAS. Similarly, in the nucleus, the recruitment of cGAS to DSBs occurs and communicates with poly [ADP‐ribose] polymerase 1 (PARP‐1) through the interaction with poly (ADP‐ribose) 190. The cGAS‐PARP1 cooperation blocks development of the PARP1–Timeless assembly, and in this way, represses HR.…”
Section: The Cgas‐sting Pathway For Tumorigenesis and Immunotherapy Rmentioning
confidence: 99%
See 2 more Smart Citations